2018
DOI: 10.31067/0.2018.35
|View full text |Cite
|
Sign up to set email alerts
|

Bilinç Durumunu Değerlendirmek İçin Kullanılabilecek Yeni Bir Ölçek: Four Skor

Abstract: Günümüzde nörolojik durumun değerlendirilmesinde en yaygın olarak kullanılan ölçek Glasgow Koma Skalası'dır (GKS). GKS'deki sınırlamalar entübe veya afazik hastalardaki verbal yanıt zorluğunu içermektedir. Full Outline of UnResponsiveness (FOUR) skoru son zamanlarda önerilen sözlü yanıta bağımlı olmayan yeni bir koma skalasıdır. Bu makalede bilinçin tanımı, seviyeleri ve bilinç düzeyini değerlendirmek için kullanılabilecek yeni bir ölçek olan Four skor tanıtılacaktır. Özellikle yoğun bakım ve acil gibi kritik … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown that the GCS is considered an adequate assessment tool among healthcare professionals because it is well established in the field (Fischer et al, 2010). In contrast, it has been reported that the FOUR Score is suitable for use by both physicians and nurses in neurological evaluation (Wolf et al, 2010), can be readily applied by healthcare professionals after basic training on its use (Karadağ Arlı, 2018), provides more detailed neurological information and can also be easily used by less experienced nurses (Surabenjawong et al, 2017). In another study, the FOUR Score was found to be simpler and more functional compared to the GCS (Ghelickhani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the GCS is considered an adequate assessment tool among healthcare professionals because it is well established in the field (Fischer et al, 2010). In contrast, it has been reported that the FOUR Score is suitable for use by both physicians and nurses in neurological evaluation (Wolf et al, 2010), can be readily applied by healthcare professionals after basic training on its use (Karadağ Arlı, 2018), provides more detailed neurological information and can also be easily used by less experienced nurses (Surabenjawong et al, 2017). In another study, the FOUR Score was found to be simpler and more functional compared to the GCS (Ghelickhani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the FOUR Score is significant superiority to the GCS and provides information about important details of neurological examination such as brainstem reflexes and respiratory response (Wolf et al, 2007; Fugate et al, 2010; Akavipat et al, 2011; Gujjar et al, 2013; Jalali & Rezaei, 2014; Gorji et al, 2014; Gorji et al, 2015; Peng et al, 2015; Sepahvand et al, 2016; Khanal et al, 2016; Keykha et al, 2017; Nyam et al, 2017; Momenyan et al, 2017; Kondizella et al, 2020). In the FOUR Score, each of the 4 domains is scored out of 4 points, thus it is believed to be easier to keep in mind and more practical than the GCS (Karadağ Arlı, 2018). Additionally, studies have shown that nurses can also comfortably apply this scale after receiving training on its use and implementation (Karadağ Arlı, 2018; Surabenjawong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation